Drugs that are abused in sport - Cowan, D. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Misuse refers to wrong or improper use whereas its synonym abuse has the connotation of a corrupt practice or custom especially one that has become chronic [Oxford English Dictionary online]. Indeed, intent is also usually implied with abuse. In the context of drugs in sport the term doping defines misuse or abuse. Evidence obtained from anti-doping analysis can clearly only identify misuse by an individual. Recently, surveillance programmes in the anti-doping context and interviewing individuals thought to be misusing drugs have provided clear evidence of abuse but it is still very rare for an athlete to admit the use of a drug. The World Anti-Doping Agency (WADA) is the international body that produces a Prohibited List each year[1] clarifying what would constitute misuse in sport thereby providing the detail to be able to control misuse. The WADA list uses a variety of standard pharmacological categories for prohibited substances plus some less widely used terms to classify the types of substance that are prohibited. The prohibition of use may be at any time or only during competition (in-competition), which is defined as being within 12 hours of a competition until the end of doping control sample collection. The main category of substances prohibited at all times is the so-called anabolic agents. This category is subdivided into anabolic androgenic steroids and other anabolic agents, that is substances with anabolic activity that do not have a steroidal structure. Other prohibited categories comprise peptide hormones, growth factors and related substances, beta-2 agonists, hormone and metabolic modulators, diuretics and other masking agents A new category called non-approved substances was added last year to the Prohibited List in order to be able to control designer drugs or drugs under development or that have been discontinued. WADA also prohibit a variety of methods some of which may involve drug administration. These methods are categorised as enhancement of oxygen transfer, chemical and physical manipulation and gene doping. The categories of substances prohibited in-competition only comprise stimulants, narcotics, cannabinoids and so-called glucocorticosteroids. Some sports also prohibit alcohol and some beta-blockers. The findings from WADA accredited laboratories are summarised each year. These figures obviously only document what has been found and not what is being misused and there is very limited reliable data relating to prevalence of misuse. Furthermore the reported findings require careful interpretation since they may be heavily influenced by apparently minor changes in the rules and/or by the sports that have been tested and by the type of competition. Over the years since figures were first compiled (initially by the International Olympic Committee), nandrolone, testosterone and salbutamol appeared to be the most widely misused of all of the substances representing about 0.3 % of samples each against an average of between 1-2 % of all samples containing a Prohibited Substance. Indeed the reporting of testosterone rocketed in 2005 probably because WADA reduced the reporting threshold, based on the ratio of testosterone (T) to its inactive epimer epitestosterone (E) in urine, from 6 to 4. Presumably this was to make the test of administration more sensitive. Although the modal T/E is about 1, the ratio of 4 is exceeded in about 3 % of the normal population (see e.g. [2]). On the other hand, Asians in particular have a lower modal value of about 0.2 and some individuals can administer testosterone without exceeding a ratio even of 4. Internationally, nandrolone findings have remained fairly consistent over the years after a relatively large number of findings in the late 1980s thought to be caused by the use of nandrolone esters especially nandrolone decanoate that has a particularly long biological half-life. In the UK, an increase to 0.29 % in 1999 from the previous twelve-year average of 0.09 % was thought to have arisen from the use by athletes of contaminated supplements[3] coupled with the fact that the International Olympic Committee reduced the reporting threshold for the nandrolone metabolite 19-norandrosterone after the Atlanta Olympic Games in 1996; thus even misuse in its generally understood sense cannot necessarily be proved by a doping control result. On the other hand, reported findings for salbutamol have dropped significantly in the last few years thought to be due simply to the fact that the reporting threshold has now been raised. The pharmacology of most of the drug classes prohibited by WADA has been covered in a special edition of the British Journal of Pharmacology[4] and diuretics in a later issue.[5] This presentation will focus on how the abuse of drugs in sport may be reduced before the forthcoming Olympic Games.